C++ and Java comparison between both languages / Syarul Emy Abu Samah - Abu Samah, Syarul Emy (2002)
The report is written after a year of doing a research by comparing two programming languages. The report are divided by several chapter, chapter 1 - is the introduction of the report. Chapter 2 is the partial of review, articles, Internet that have been compiled to support this research. It includes the historical background of both languages, the characteristics of the languages, differences between languages and lastly the research that had been done. In Chapter 2, explains the methodologies that have been used to implement this research. It includes the types of program used, hardware and software, the specific area of research and lastly my workflow (explain in Gantt Chart). The chapter 4 is the findings, the way in which 1 get the raw data, results and analysis to explain this raw data, the future works, conclusion and the recommendation for this research project. Chapter 5 is for the bibliography that helps in this research project. The report also has 5 types of appendices. In Appendix A, is the Gant Chart. The Appendix B, is the raw data. The Appendix C, is the compilation of raw data. This raw data has been tablized in their criteria. In Appendix D, shows the compilation of data that has been converts to the Graph formats. The Appendix E, is for the codes use in the research project.